Protonophores induce plastoquinol oxidation and quench chloroplast fluorescence: Evidence for a cyclic, proton-conducting pathway in oxygenic photosynthesis - McCauley, Steven W. (1987)
The photosynthetic apparatus converts light into chemical energy by a series of reactions that give rise to a coupled flow of electrons and protons that generate reducing power and ATP, respectively. A key intermediate in these reactions is plastoquinone (PQ), the most abundant electron and proton (hydrogen) carrier in photosynthetic membranes (thylakoids). PQ ultimately transfers electrons to a terminal electron acceptor by way of the Rieske Fe-S center of the cytochrome bf complex. In the absence of a terminal acceptor, electrons accumulate in the PQ pool, which is reduced to plastoquinol (PQH(2)), and also on a specialized PQ, Q(A), which is reduced to an unprotonated semiquinone anion (Q(A)(-)). The accumulation of Q(A)(-) is measured by a rise in fluorescence yield and the accumulation of PQH(2) is measured by absorption difference spectrometry. We have found that in the absence of a terminal electron acceptor, two chemically diverse proton-conducting ionophores (protonophores), 2,6-di-t-butyl-4-(2′,2′-dicyanovinyl)phenol (SF 6847) and carbonylcyanide p-trifluoromethoxyphenylhydrazone (FCCP), induced oxidation of PQH(2) and quenching of chloroplast fluorescence, signifying oxidation of Q(A)(-). The two protonophores produced the same effects even when the only recognized pathway of PQH(2) oxidation by way of the cytochrome bf complex was inhibited by dibromothymoquinone. Two other uncouplers, gramicidin and nigericin, which are not protonophores but facilitate proton movement across membranes by other mechanisms, were ineffective. These findings are consistent with the operation in the oxygen-generating photosystem (photosystem II) of a cyclic, proton-conducting pathway.